2007
DOI: 10.1590/s1806-83242007000400005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the effectiveness of the chemomechanical preparation against Enterococcus faecalis after single- or multiple-visit root canal treatment

Abstract: The purpose was to assess the elimination of Enterococcus faecalis in vitro in human mandibular premolars after chemomechanical preparation with or without the use of a calcium hydroxide dressing. After 60 days of contamination with E. faecalis, the root canals were prepared using the Crown-Down technique combined with 2% chlorhexidine gel irrigation. Then, the specimens were divided into two experimental groups, treated in a single visit or in multiple visits, and two control groups. The multiple-visit group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
1
14
0
5
Order By: Relevance
“…21 To decrease the amount of leakage and bacterial contaminations, medicaments are added in the pulp canal space. 22 Except for subgroups containing Cavit with chlorhexidine (CHX) and specimens in subgroups CHX with IRM, all other samples showed a comparatively higher leakage in group without intrapulp medicaments as compared with other groups (Tables 4 to 7). We also observed that subgroups containing calcium hydroxide (CaOH) with Coltosol and CaOH with Cavit showed the presence of minimal microleakage up to 3 weeks' time.…”
Section: Discussionmentioning
confidence: 94%
“…21 To decrease the amount of leakage and bacterial contaminations, medicaments are added in the pulp canal space. 22 Except for subgroups containing Cavit with chlorhexidine (CHX) and specimens in subgroups CHX with IRM, all other samples showed a comparatively higher leakage in group without intrapulp medicaments as compared with other groups (Tables 4 to 7). We also observed that subgroups containing calcium hydroxide (CaOH) with Coltosol and CaOH with Cavit showed the presence of minimal microleakage up to 3 weeks' time.…”
Section: Discussionmentioning
confidence: 94%
“…A outra abordagem consiste na eliminação das bactérias remanescentes ou em torná-las inofensivas por sepultamento após uma obturação hermética tridimensional, para privar a nutrição dos micro-organismos e o espaço necessário para sobreviver e se multiplicar 15,16 . Contudo, nem o tratamento em sessão única nem o de sessão múltipla podem eliminar completamente as colônias microbianas 17 . Em relação à redução de endotoxinas, o tratamento em sessão única mostrou-se menos eficaz do que em sessões múltiplas 18 .…”
Section: Revisão De Literaturaunclassified
“…[24] This microorganism was chosen as the bacteriological marker in this study because of its reported resistance to chemomechanical procedures. It is often involved in persistent endodontic infections and periradicular infl ammation and is often found existing in monocultures.…”
Section: E Faecalis Is a Non-fastidious Easy-to-grow Facultative Anmentioning
confidence: 99%